Soekarno Hatta Airport Social Fund Application in PT. Angkasa Pura - Desy Apriani; Devi Kusumawardhani; Yazid Ma'ruf (Universitas Raharja, 2022)
The development of technology is currently growing rapidly so that many attract the attention of the wider community. The development of computers is constantly dynamic and requires information that is fast, precise and systematic and does not require a long time. Therefore, the processing of social funds plays a very important role in the financial process in the company. Social funds are gifts in the form of money provided or collected with the aim of helping the social needs of the company. Processing social funds still uses Ms. Excel is running less than the maximum due to input and expense input errors so that the report is out of sync. Therefore, there needs to be a social fund processing system to manage these funds to be synchronous. The research method used consisted of data collection methods, namely observation, interviews and literature study. For analysis using the PIECES analysis method. This system uses the PHP programming language and MySQL database. The system design uses the design of the UML (Unified Modeling Language) model. The testing method used is the Blackbox Testing method. The results obtained from this study are a social fund processing application system that helps companies in terms of fund management